Tradução e adaptação da escala de potencial de ajustamento intercultural para a realidade brasileira - Tashima, Jesselyn Nayara (2011)
This study aimed to adapt the Intercultural Adjustment Potential Scale (ICAPS), developed by Matsumoto and LeRoux (2006) to the Brazilian context. The purpose of this instrument is to predict the degree of difficulty a person will have in adjusting to a new culture. In this study, it was opted to work with the 26 items captured by the four factors (emotion regulation, flexibility, openness, critical thinking). The adaptation process followed five steps: translation to Portuguese, back translation to English, semantic analysis by expert committee and pretest of the ICAPS version in Portuguese and administration of the instrument to the target population in order to conduct the cultural adaptation of the scale to the Brazilian context and to verify the psychometrics properties. The sample consisted of 428 students from a Federal University from Triângulo Mineiro and from other Private Educational Institution of Uberlândia, the age varied between 14 and 46 (mean= 19.21, standard deviation= 3.97). The data were submitted to reliability calculation of the original factors of ICAPS and to factorial analysis needed for the adaptation and validation of the instrument. The factorial structure was composed by 4 factors that accounted for 30.78% of the total variance. The reliability for the factor Emotion Regulation was 0.10; for the factor Openness was -0.35, for the factor Flexibility was -0.04 and for the factor Critical Thinking was 0.45. The results pointed for a structure with no empirical support for the Brazilian context. It were discussed the theoretical limitations to the construct and possible flaws of the construction of the instrument. This study has the purpose to encourage new researches involving intercultural adjustment and psychological instruments.